(untitled) (Al-Academy, 2023)
The theatrical image represents one of the tools of communication with the other to create a communicative language that is produced and transmitted by the actor and his body through the theatrical space to convey the meaning in all its forms and types. The actor is concerned with the composition and construction of these images. My girl, the image is fragmented and multiple and different. Therefore, based on the foregoing, the researcher has divided his research into four chapters, representing the (methodological framework). First, the research problem, which is manifested in the following question (what is the structure of the fragmented image of the actor’s performance? The Iraqi playwright), and secondly: the importance of the research, the need, the goal of the research, the limits of the research, and (theoretical framework) with two sections that included the first topic: the composition of the theatrical image / while the second topic came: the fragmented image of the performance of the Iraqi theatrical actor) and concluded with the indicators that resulted from the theoretical framework. The (research procedures) included an analysis of the research sample chosen by the researcher intentionally, which is represented by the play (Ahriman), while (results, discussion and conclusions), a set of results emerged that the researcher came out with:1. The show activated the synthetic and intellectual image according to fixed and variable connotations that worked on broadcasting a set of functions by means of metaphor for the vocabulary through new symbols that can be interpreted, achieved by the performative act of the actor, while highlighting the functioning and moving of the meaning and its messages.